Racialization, Racism, and Anti-Racism in the Nordic Countries - Hervik, Peter (Approaches to Social Inequality and Difference,, 2019)
This book represents a comprehensive effort to understand discrimination, racialization, racism, Islamophobia, anti-racist activism, and the inclusion and exclusion of minorities in Nordic countries. Examining critical media events in this heavily mediatized society, the contributors explore how processes of racialization take place in an environment dominated by commercial interests, anti-migrant and anti-Muslim narratives and sentiments, and a surprising lack of informed research on national racism and racialization. Overall, in tracing how these individual events further racial inequalities through emotional and affective engagement, the book seeks to define the trajectory of modern racism in Scandinavia. .